2019
DOI: 10.3389/fneur.2019.00001
|View full text |Cite
|
Sign up to set email alerts
|

Association Between HLA Genotype and Cutaneous Adverse Reactions to Antiepileptic Drugs Among Epilepsy Patients in Northwest China

Abstract: This study aimed to investigate the association between HLA genotypes and antiepileptic drug-induced cutaneous adverse reactions (AEDs-cADRs) among patients with epilepsy in Ningxia Hui Autonomous Region of Northwest China. Fifteen patients with AEDs-cADRs and 30 matched AEDs tolerant controls from anested case-control study were tested the HLA-A, HLA-B, and HLA-DRB1 genotype using the polymerase chain reaction sequence-based typing (PCR-SBT). Significant difference was not observed between AEDs-cADRs and AEDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 20 publications
5
115
3
Order By: Relevance
“…Typical infections are seen in immunocompromised hosts such as transplant recipients, oncology, and pediatric patients, where it manifests itself as a subcutaneous disease and rarely as deep mycoses [9,[22][23][24][25][26]. Particularly in East Asia, E. dermatitidis was detected in disseminated and neurotropic infections with high mortality [11,27]. Note, however, that despite infections occurring in apparently healthy humans, some authors concluded that E. dermatitidis and related species are opportunists rather than pathogens [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Typical infections are seen in immunocompromised hosts such as transplant recipients, oncology, and pediatric patients, where it manifests itself as a subcutaneous disease and rarely as deep mycoses [9,[22][23][24][25][26]. Particularly in East Asia, E. dermatitidis was detected in disseminated and neurotropic infections with high mortality [11,27]. Note, however, that despite infections occurring in apparently healthy humans, some authors concluded that E. dermatitidis and related species are opportunists rather than pathogens [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study has shown that hypertension, prior symptomatic stroke and chronic infarcts on MRI were independently associated with recurrent stroke and this also doubled the all-cause mortality [11]. However, an artificial neural network model utilizing 19 independent variables generated only a moderate accuracy of 75% for predicting stroke recurrence at 1-year [12].…”
Section: Introductionmentioning
confidence: 99%
“…longitudinally. This was one reason the STAI was also included, since it has been extensively validated in healthy populations, has been suggested for use in PD by the Movement Disorder Society, and has been proven to be sensitive to change in numerous studies [46][47][48].…”
Section: Plos Onementioning
confidence: 99%